Laurel Brinton y Elizabeth Closs Traugott. Lexicalization and language change - Rojas Gallardo, Darío (Boletín de Filología, 2008)
LAUREL BRINTON Y ELIZABETH CLOSS TRAUGOTT. Lexicalization and language change. Cambridge: University Press. 2005, 207 páginas.